Behavior of the Study Plan of the Medical School of the Faculty of UTA Health Sciences. Curriculum Redesign Proposal - Dra Ena V González Gutiérre (2010)
Higher Medical Education reflects the development of the medical sciences and their teaching; It must cover a wide spectrum of competencies based on a solid scientific-technical and ethical-humanistic training that allows them to investigate and attend to the health problems of the individual and the population (community), while updating and increasing their knowledge and modes of action. Taking into account the above and with the objective of analyzing whether the plans and study programs of the Medicine career of the Faculty of Health Sciences of the Technical University of Ambato respond to the current demands of the Medical Sciences graduate, guaranteeing that there is competence and performance to solve the health problems of society, we took on the task of carrying out this study, conducting a bibliographic review on the design of study plans and programs, reviewing the plans and programs of the Medicine career at the Technical University of Ambato. Surveys were also carried out on the first group of graduates of the Medicine career. When analyzing the results, we observe that in general there is mastery of the main skills in the graduates and that those that show greater difficulties are determined, to some extent, by the scarcity or difficulty in acquiring diagnostic equipment (otoscope, ophthalmoscope) by students. Compared to the development of medical education, a considerable degree of correspondence can be seen in different points studied in the study program, according to our social and health reality. All these conceptual elements can contribute to a more complete reelaboration of the current Medicine curriculum, which, although it has been fulfilled, is in need of a profound transformation.